The landscape of alternative polyadenylation during EMT and its regulation by the RNA-binding protein Quaking - Daniel P. Neumann; Katherine A. Pillman; B. Kate Dredge; Andrew G. Bert; Caroline A. Phillips; Rachael Lumb; Yesha Ramani; Cameron P. Bracken; Brett G. Hollier; Luke A. Selth; Traude H. Beilharz; Gregory J. Goodall; et al. (RNA Biology)
Epithelial-mesenchymal transition (EMT) plays important roles in tumour progression and is orchestrated by dynamic changes in gene expression. While it is well established that post-transcriptional regulation plays a significant role in EMT, the extent of alternative polyadenylation (APA) during EMT has not yet been explored. Using 3’ end anchored RNA sequencing, we mapped the alternative polyadenylation (APA) landscape following Transforming Growth Factor (TGF)-β-mediated induction of EMT in human mammary epithelial cells and found APA generally causes 3’UTR lengthening during this cell state transition. Investigation of potential mediators of APA indicated the RNA-binding protein Quaking (QKI), a splicing factor induced during EMT, regulates a subset of events including the length of its own transcript. Analysis of QKI crosslinked immunoprecipitation (CLIP)-sequencing data identified the binding of QKI within 3’ untranslated regions (UTRs) was enriched near cleavage and polyadenylation sites. Following QKI knockdown, APA of many transcripts is altered to produce predominantly shorter 3’UTRs associated with reduced gene expression. These findings reveal the changes in APA that occur during EMT and identify a potential role for QKI in this process.